2021
DOI: 10.1101/2021.06.10.21258709
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effectiveness and Safety of Niclosamaide as Add-on Therapy to the Standard of Care Measures in COVID-19 Management: Randomized controlled clinical trial

Abstract: Background: COVID-19 pandemic has ignited the urge for repurposing old drugs as candidate antiviral medicines to treat novel challenges of viral infections. Niclosamide (NCS) is an anti-parasitic drug of known antiviral potential. Therefore, this study attempts to investigate the antiviral effect and safety of NCS on SARS-CoV-2 caused COVID-19 patients. Methods: Randomized controlled open label clinical trial encompassed 75 COVID-19 patients treated with standard of care plus NCS were included as experimental … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…However, other studies did not report statistically significant differences in mortality ( Ravikirti and Pattadar, 2021 ), length of hospitalization ( Abdulamir et al, 2021a ) and clinical endpoints, disease progression, recovery, the occurrence of symptoms ( Okumuş et al, 2021 ). The study authors did not recommend the routine use of ivermectin in COVID-19 patients, limiting its use to a clinical trial.…”
Section: Other Agents Tested For Potential Efficacy In Treating Covid-19 Infectionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, other studies did not report statistically significant differences in mortality ( Ravikirti and Pattadar, 2021 ), length of hospitalization ( Abdulamir et al, 2021a ) and clinical endpoints, disease progression, recovery, the occurrence of symptoms ( Okumuş et al, 2021 ). The study authors did not recommend the routine use of ivermectin in COVID-19 patients, limiting its use to a clinical trial.…”
Section: Other Agents Tested For Potential Efficacy In Treating Covid-19 Infectionmentioning
confidence: 95%
“… Drug No. patients Dose Outcome Effect Ivermectin ( AFMZ et al, 2021 ) 1,788 140 - 400 µg/kg Mortality reduction RR = 0.39 (95% CI: 0.20 - 0.74); p = 0.004 Colchicine ( Golpour et al, 2021 ) 5,901 NA Mortality reduction RR = 0.644 (95% CI: 0.555 – 0.748) Niclosamide ( Abdulamir et al, 2021a ) 150 3 g per day Reduced recovery time p ≤ 0.05 Tofacitinib ( Gunay et al, 2021 ) 289 10 mg twice a day Mortality reduction HR = 0.49 (95% CI: 0.15 to 1.63) Bamlanivimab - Etesevimab ( Dougan et al, 2021 ) 1,035 2.8 g + 2.8 g Hospitalizations or death absolute risk difference = −4.8%; (95% CI − 7.4 - −2.3); RR = 0.3; p < 0.001 Bamlanivimab - Etesevimab ( Gottlieb et al, 2021 ) 577 2.8 g + 2.8 g Viral load Viral load change = - 0.57 (95% CI: −1.00 to −0.14); p = 0.01 Anticoagulants ( Parisi et al, 2021 ) 25,719 therapeutic and prophylactic dose Mortality reduction RR = 0.50 (95% CI: 0.40 - 0.62) ASA ( RECOVERY Collaborative Group, 2021 ) 14,892 150 mg Mortality reduction RR = 0.96 (95% CI 0.89 – 1.04); p = 0.35 …”
Section: Other Agents Tested For Potential Efficacy In Treating Covid-19 Infectionmentioning
confidence: 99%
“…The results of this study showed that the UNI91104 is a promising and safe anti-COVID-19 drug candidate following intranasal administration [168]. (b) Another study comprised 75 COVID-19 patients who received SOC plus niclosamide in the experimental group and 75 COVID-19 patients who received only SOC therapy as a control group [169]. Within 30 days of follow-up, there was no significant difference in the incidence of death versus recovery between the two research groups.…”
Section: Niclosamidementioning
confidence: 81%
“…The niclosamide supplement group's median survival time to cure was considerably shorter than the control group. After adjusting for comorbidity count, niclosamide add-on treatment increased the chance of cure by 60% each day compared to the control group [169].…”
Section: Niclosamidementioning
confidence: 89%
“…After abstract screening and full-text reading, 152 RCTs were included in the analysis. All 152 RCTs were posted on the medRxiv server …”
Section: Resultsmentioning
confidence: 99%